2012
DOI: 10.1182/blood-2011-05-352666
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of histone H2A-deubiquitinase Mysm1 in hematopoiesis and lymphocyte differentiation

Abstract: Stem cell differentiation and lineage specification depend on coordinated programs of gene expression, but our knowledge of the chromatin-modifying factors regulating these events remains incomplete. Ubiquitination of histone H2A (H2A-K119u) is a common chromatin modification associated with gene silencing, and controlled by the ubiquitin-ligase polycomb repressor complex 1 (PRC1) and H2A-deubiquitinating enzymes (H2A-DUBs). The roles of H2A-DUBs in mammalian development, stem cells, and hematopoiesis have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 50 publications
(70 reference statements)
8
121
0
Order By: Relevance
“…31,32 Together, these data add more to the finding of Nijnik et al 32 by demonstrating that Mysm1 is required for differentiation of HSC, specifically during the transition to MPPs.…”
Section: Consistently Mysm1supporting
confidence: 56%
See 2 more Smart Citations
“…31,32 Together, these data add more to the finding of Nijnik et al 32 by demonstrating that Mysm1 is required for differentiation of HSC, specifically during the transition to MPPs.…”
Section: Consistently Mysm1supporting
confidence: 56%
“…Nijnik et al 32 recently reported the role of Mysm1 in BM hematopoiesis and function. In this study, we attempted to investigate the importance of Mysm1 in HSC differentiation and function in a more detailed manner.…”
Section: Mysm1 Controls Hsc Differentiation During Its Transition To mentioning
confidence: 99%
See 1 more Smart Citation
“…Orchestration of histone modifications by MYSM1 has recently been shown to function as part of an epigenetic switch controlling B-cell development (107). Accordingly, mice deficient in MYSM1 show defects in lymphocyte and erythroid development (188).…”
Section: E Jamm Familymentioning
confidence: 99%
“…[1][2][3][4] Moreover, the variants in this locus have been shown to strongly affect the severity of sickle cell disease and thalassemia, emphasizing their clinical importance. 2,[5][6][7] The associated region is intergenic between 2 genes: HBS1L and MYB.…”
Section: © 2013 By the American Society Of Hematologymentioning
confidence: 99%